2021
DOI: 10.1109/access.2021.3082932
|View full text |Cite
|
Sign up to set email alerts
|

Foundations and Modeling of Dynamic Networks Using Dynamic Graph Neural Networks: A Survey

Abstract: Dynamic networks are used in a wide range of fields, including social network analysis, recommender systems and epidemiology. Representing complex networks as structures changing over time allow network models to leverage not only structural but also temporal patterns. However, as dynamic network literature stems from diverse fields and makes use of inconsistent terminology, it is challenging to navigate. Meanwhile, graph neural networks (GNNs) have gained a lot of attention in recent years for their ability t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
128
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(130 citation statements)
references
References 83 publications
(190 reference statements)
0
128
0
2
Order By: Relevance
“…For example, networks may be polarized (Lofdahl et al, 2015 ), hierarchical (Giabbanelli, 2011 ), planar (Giabbanelli, 2010 ), or dynamic. This diversity is exemplified in generators of dynamic networks, which use methods as varied as stochastic blockmodels (Kim et al, 2018 ), graph neural networks (Skardinga et al, 2021 ), or event models (Fritz et al, 2020 ). A potential follow-up study could thus extend our approach by including network properties to assess whether they have pronounced effects on the cost of computing various measures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, networks may be polarized (Lofdahl et al, 2015 ), hierarchical (Giabbanelli, 2011 ), planar (Giabbanelli, 2010 ), or dynamic. This diversity is exemplified in generators of dynamic networks, which use methods as varied as stochastic blockmodels (Kim et al, 2018 ), graph neural networks (Skardinga et al, 2021 ), or event models (Fritz et al, 2020 ). A potential follow-up study could thus extend our approach by including network properties to assess whether they have pronounced effects on the cost of computing various measures.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, multiple interesting literature surveys and reviews [1][2][3][4][5][6][7][8][9] have been done which shown the length and breadth of this emerging area. This is accompanied by their rich and growing research application in natural sciences, recommender systems, or day-to-day use systems (traffic networks, social networks, computer networking).…”
Section: Introductionmentioning
confidence: 99%
“…Representation learning on temporal interaction networks has gradually become a hot topic in the research of machine learning [24]. A key challenge of modeling temporal interaction networks is how to capture the evolution of user interests and item features effectively.…”
Section: Introductionmentioning
confidence: 99%